2011
DOI: 10.1186/1475-2875-10-349
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a six-dose regimen of artemether-lumefantrine among uncomplicated Plasmodium falciparum patients in the Tigray Region, Ethiopia

Abstract: BackgroundIn 2004, Ethiopia switched its first-line treatment of uncomplicated Plasmodium falciparum malaria from sulphadoxine-pyrimethamine to a fixed artemisinin-based combination therapy (ACT), artemether-lumefantrine (AL). Patient adherence to AL regimen is a major determining factor to achieve the desired therapeutic outcome. The aim of this study was to measure patient adherence levels to the six-dose AL regimen for the treatment of uncomplicated P. falciparum malaria and to identify its determinant fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(98 citation statements)
references
References 24 publications
8
85
4
1
Order By: Relevance
“…Several important recent public sector studies, however, find adherence results close to or lower than the levels we report here [25,27,35,37,38]. It is hard to infer adherence rates among retail sector patients from these studies, however, since the types of patients, illnesses and services provided in the retail sector could differ substantially.…”
Section: Discussioncontrasting
confidence: 80%
“…Several important recent public sector studies, however, find adherence results close to or lower than the levels we report here [25,27,35,37,38]. It is hard to infer adherence rates among retail sector patients from these studies, however, since the types of patients, illnesses and services provided in the retail sector could differ substantially.…”
Section: Discussioncontrasting
confidence: 80%
“…However, adherence to AL by “timely completion” was high in three studies (88.3%–100%) [15], [22], [33] in contrast with studies of SP + amodiaquine (37.7%) [65] and SP + artesunate (76.6%) [23]. By “verified timely completion” adherence to AL was similar in three studies (38.7%–65%) [18], [28][29] to adherence to other ACTs (39.4%–75%) [17], [20], [23] and higher in two other studies (90%–93%) [19], [61].…”
Section: Resultsmentioning
confidence: 84%
“…However, among studies of AL, adherence by “verified timely completion” (38.7%–65%) [18], [28][29] was lower compared to “timely completion” (88.3%–100%) [15], [22], [33], except in studies where the research team enrolled patients at the time the drug was obtained and likely had a more significant research presence than in other studies (90% and 93%) [19], [61]. Similarly, adherence to AL by “verified completed treatment” (64.1%–83%) [16], [24], [27], [29], [60] tended to be lower than for “completed treatment” (67%–100%) [22], [28], [36], [38], [57][58], with the exception of two household surveys without pill counts with adherence of 47% [41], [46].…”
Section: Resultsmentioning
confidence: 99%
“…For example, patients may not understand how to correctly take the medication, 45,56-60 they may forget to take their pills, 18,56,58,59 they may be saving some pills for a future malaria episode, 45,56 or they may stop taking the medication once they feel better. 61,62 In our study, we found no relationship between literacy or education and adherence, and we also found that 91% of patients took the first two doses of AL with the correct number of pills at approximately the correct time (data not shown). This suggests that noncomprehension of dosing may not be the major driver of nonadherence.…”
Section: Discussionmentioning
confidence: 69%